Relationship between Military Expenditure and Economic Growth in ASEAN: Evidence from Indonesia - Chairil, Tangguh; Sinaga, Dedy; Febrianti, Annisa (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
World military expenditure in post-Cold War world shows increasing trend especially in ASEAN region; Indonesia is no exception. The trend may have been supported by the argument that military expenditure has positive multiplier effects on economic growth. Unfortunately, there have been not too many studies on the effect of military expenditure on economic growth in the Indonesia context. This paper examines the topic by first reviewing literature on the relationship between military expenditure and economic growth, then by empirically testing the causal relationship between the two variables by using the Augmented Sollow Growth Model. The result shows that Indonesia's military expenditure has positive effect on the country's economic growth, which is most possibly caused by development of human capital as effect of military expenditure.